Age-Predicted Maximal Heart Rate in Recreational Marathon Runners: A Cross-Sectional Study on Fox's and Tanaka's Equations - Nikolaidis, Pantelis T.; Rosemann, Thomas; Knechtle, Beat (Frontiers in Physiology, 2018)
Age-based prediction equations of maximal heart rate (HRmax), such as the popular formulas Fox’s 220-age or Tanaka’s 208-0.7×age, have been widely used in various populations. Surprisingly, so far these equations have not been validated in marathon runners, despite the importance of the role of HRmax for training purposes in endurance running. The aim of the present study was to examine the validity of Fox and Tanaka equations in a large sample of women and men recreational marathon runners. Participants (n=180, age 43.2±8.5 years, VO2max 46.8 mL/min/kg, finishers in at least one marathon during the last year) performed a graded exercise test on a treadmill, where HRmax was measured. Measured HRmax correlated largely with age in the total sample (r = -0.50, p < 0.001), women (r = -0.60, p < 0.001) and men (r = -0.53, p < 0.001). In women, a large main effect of method on HRmax (p = 0.001, η2 = 0.294) was shown with measured HRmax lower than Fox-HRmax (-4.8 bpm; -8.4, -1.3) and Tanaka-HRmax (-4.9 bpm; -8.1, -1.8). In men, a moderate effect of assessment method on HRmax was found (p = 0.001, η2 = 0.066) with measured HRmax higher than Fox-HRmax (+2.8; 1.0, 4.6), Tanaka-HRmax higher than Fox-HRmax (+1.2; 0.7, 1.7). Based on these findings, it was concluded that Fox and Tanaka’ formulas overestimated HRmax by ~5 bpm in women, whereas Fox underestimated HRmax in men by ~3 bpm. Thus, we recommend the further use of Tanaka’s formula in men marathon runners. In addition, exercise physiologists and sport scientists should consider the observed differences among various assessment methods when performing exercise testing or prescribing training program relying on HR.